Odnos otvorenosti prema iskustvu i uspješnog starenja : provjera posredujuće uloge životnih žaljenja - Tucak, Ivana, psihologinja (Array, 2018)
The aim of the research was to explore the relationship between openness to experience and successful aging, and to test potential mediation role of life regrets due to missed opportunities and faulty actions in that relationship. The growth of proportion of older people in the population prompted the research interest for factors that contribute longevity and quality of life in old age, and in that context, the number of studies focused on successful or good ageing has increased. Successful ageing is a very complex construct and the consensus regarding its components and measurement is not yet reached. Openness to experience refers to dimension of personality that includes aesthetic appreciation, inquisitiveness, creativity, and unconventionality, and, as such, it was hypothesized that it could contribute to successful ageing. Four hundred and seventy-nine subjects, 60 to 95 years old, from various regions of Croatia, have participated in the study. Successful ageing was operationalized in two ways: by The Self-Rated Successful Ageing Scale and by a composite measure of successful ageing. This measure is based on the components of the Cho, Martin and Poon's model (2012), i.e. subjective health status, perception of financial situation and subjective well-being. Openness was measured by Croatian version (Babarović & Šverko, 2013) of openness to experience subscale from the HEXACO-PI-(R) personality measure (Ashton & Lee, 2008, 2009), while life regrets of action and inaction were measured by one question each. The results have shown that openness to experience correlated moderately high with both measures of successful ageing, while regrets of action and inaction correlated significantly and negatively with successful ageing measures. The results of testing the mediation role of life regrets in relationship between openness to experience and successful ageing showed that regrets of action were not a mediator in this relationship, while regrets of i